2018
DOI: 10.1093/rap/rky006
|View full text |Cite
|
Sign up to set email alerts
|

IL23R gene variants in relation to IL17A levels and clinical phenotype in patients with ankylosing spondylitis

Abstract: Background IL23 receptor (IL23R) binding by IL23 is required for the maturation of CD4 + cells into Th17 cells and subsequent generation of IL17A and TNF. As IL23R variations contribute to AS susceptibility, we investigated the effect of IL23R variants on cytokine levels and disease measures in an AS cohort. Methods This was a cross-sectional study of AS patients ( n = 334, 90% B27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(29 reference statements)
1
1
0
1
Order By: Relevance
“…In our study, we obtained similar results to those obtained by Pidasheva et al, Di Meglio et al and J.C Nossent et al [ 24 , 59 , 60 ], confirming the association of IL-23- R381Q polymorphism with MS under the codominant model after adjustment for age, gender and smoking factors as covariates, as well as after correcting for multiple testing using the FDR method. The presence of the IL-23- R381Q heterozygous genotype can be protective for MS development.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we obtained similar results to those obtained by Pidasheva et al, Di Meglio et al and J.C Nossent et al [ 24 , 59 , 60 ], confirming the association of IL-23- R381Q polymorphism with MS under the codominant model after adjustment for age, gender and smoking factors as covariates, as well as after correcting for multiple testing using the FDR method. The presence of the IL-23- R381Q heterozygous genotype can be protective for MS development.…”
Section: Discussionsupporting
confidence: 91%
“…These results were also reported in a study conducted by Sarin et al in inflammatory diseases (IBD and psoriasis), in which they concluded that IL-23- R381Q variant may confer protection against autoimmunity and excessive inflammation [ 58 ]. Moreover, Pidasheva et al, Di Meglio et al, Nossent et al, confirmed the protective role of the IL-23- R381Q for AS, psoriasis and Crohn disease (CD) [ 24 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 97%
“…O gene IL23R possui papel significativo em doenças como: doença de Crohn, artrite psoriática, colite ulcerativa, e recentemente, a hanseníase (Hong et al, 2019;Nossent;Sagen-Johnsen;Bakland, 2018;Sakono et al, 2020;Li et al, 2016) (OR: 0,69, P-valor: 3,27×10 -11 ) que apresentou associação a menor risco a doença.…”
Section: Gene Il23r E a Hanseníaseunclassified